2021
DOI: 10.3390/cancers13030488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-Year Hospital Volume on Surgical Margin and Biochemical-Failure-Free Survival in Patients Undergoing Robotic versus Nonrobotic Radical Prostatectomy: A Nationwide Cohort Study from the National Taiwan Cancer Database

Abstract: Purpose: To examine the effect of hospital volume on positive surgical margin (PSM) and biochemical-failure-free survival (BFS) rates in patients with prostate cancer (PC) undergoing robotic-assisted or nonrobotic-assisted radical prostatectomy (RP). Patients and Methods: The patients were men collected in the National Taiwan Cancer Registry diagnosed as having PC without distant metastasis who received RP from 44 multi-institutes in Taiwan. The logistic regression method was used to analyze the risk from RP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“… 12 , 13 , 32 The lack of differences in the blood transfusion volume among the 3 RP techniques may be due to the hospital volume effect. 6 In Taiwan, traditional ORP has been performed by highly experienced surgeons for many years, 5 , 6 , 33 which may have minimized the blood volume required for transfusion. Because LRP and RARP are designed to require a low volume of blood for transfusion and because this surgery is conducted in low-volume hospitals, their transfusion volume may not be significantly different in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 , 13 , 32 The lack of differences in the blood transfusion volume among the 3 RP techniques may be due to the hospital volume effect. 6 In Taiwan, traditional ORP has been performed by highly experienced surgeons for many years, 5 , 6 , 33 which may have minimized the blood volume required for transfusion. Because LRP and RARP are designed to require a low volume of blood for transfusion and because this surgery is conducted in low-volume hospitals, their transfusion volume may not be significantly different in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 17 The TCRD of the Collaboration Center of Health Information Application contains detailed patient information, such as clinical stage, pathological stage, surgical margin status, surgical procedures, treatment techniques, radiotherapy, chemotherapy regimens, and follow-up visits. 5 , 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Our protocols were reviewed and approved by the institutional review board of Tzu-Chi Medical Foundation. Patient consent was waived because data files are deidentified by scrambling the identification codes of both patients and medical facilities and sent to the National Health Research Institutes to form the original files of NHIRD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Death Registry data are additionally linked to the NHIRD to verify the cause of death and vital status of each patient. The TCRD contains detailed information, such as AJCC stages, surgical procedures, techniques, RT, hormone treatments, and pathologic stages [19][20][21][22][23][24][25][26].…”
Section: Databasementioning
confidence: 99%
“…They found no significant differences in the positive surgical margin and biochemical recurrence rate among patients who underwent open, laparoscopic, or robot-assisted radical prostatectomy after propensity score adjustment. They further examined the effect of hospital volume on positive surgical margin and biochemical recurrence-free survival rates in patients with prostate cancer undergoing robot-assisted or non-robot-assisted radical prostatectomy [3]. They found that hospital volume significantly affected positive surgical margin rates and biochemical recurrence-free survival rates and concluded that robot-assisted radical prostatectomy should be performed in a relatively high-volume hospital (>100 patients/year), if patients with prostate cancer want to receive it.…”
mentioning
confidence: 99%